The Politics of Reformation : Benjamin Bailey and the CMS in the Ecclesiastical Development of Travancore - McKee, Gary, (Religious Studies, Theology and Philosophy E-Books Online, Collection 2024., 2024)
In this book you will learn of the unheralded CMS missionary Benjamin Bailey. You willl hear the story through unpublished archive material combined with rare accounts from an Indian perspective. You will see how church reformation in India was aided by Western involvement but retained indepence from it. You will learn how the story of colonial politics and church reform are intertwined but never straightforward. For practitioners today there is much food for thought in this account.